2015
DOI: 10.1039/c4ra13399d
|View full text |Cite
|
Sign up to set email alerts
|

Optical enhancement of plasmonic activity of catalytic metal nanoparticles

Abstract: Plasmon-assisted direct photocatalysis through enhanced light absorption in catalytic metal nanoparticles. Enhancement is achieved by coupling the plasmon resonance of a silver nanoantenna to that of a catalytic metal nanoparticle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…However, their optical spectra explain the reason for this behavior. 23 The observed enhancement order is the same as that of the plasma frequencies as observed qualitatively based on absorption efficiencies. Ru has the largest plasma frequency and correspondingly has large absorption enhancement.…”
Section: Coupled Nanostructures With Large Catalytic Metal Elementssupporting
confidence: 65%
See 1 more Smart Citation
“…However, their optical spectra explain the reason for this behavior. 23 The observed enhancement order is the same as that of the plasma frequencies as observed qualitatively based on absorption efficiencies. Ru has the largest plasma frequency and correspondingly has large absorption enhancement.…”
Section: Coupled Nanostructures With Large Catalytic Metal Elementssupporting
confidence: 65%
“…Thus, shifting their plasmonic activity into the visible spectrum is important from an applications point of view. 22,23 Here, we show how to do just this using hybridized hetero-metallic nanostructures 24 which utilize a low-loss nanoantenna to collect incident light and direct it into LSPRs on the catalytic metal nanoparticles.…”
Section: Increasing Light and Plasmon Absorption In Catalytic Metalsmentioning
confidence: 99%
“…Increasing transition metal nanoparticle size redshifts optical absorption, but it increases cost and reduces surface area, and therefore catalytic activity. Recently, it has been shown that plasmonic nanoparticles can be used to increase optical absorption in adjacent nanoparticles (19)(20)(21)(22), for instance, enabling hydrogen detection (23,24).Previous reports of photocatalytic transformation in plasmonic metal nanoparticle systems rely on the metal to double as both the Significance Plasmon-enhanced photocatalysis holds significant promise for controlling chemical reaction rates and outcomes. Unfortunately, traditional plasmonic metals have limited surface chemistry, while conventional catalysts are poor optical absorbers.…”
mentioning
confidence: 99%
“…Increasing transition metal nanoparticle size redshifts optical absorption, but it increases cost and reduces surface area, and therefore catalytic activity. Recently, it has been shown that plasmonic nanoparticles can be used to increase optical absorption in adjacent nanoparticles (19)(20)(21)(22), for instance, enabling hydrogen detection (23,24).…”
mentioning
confidence: 99%
“…Most of the previous investigations were limited to dimers with ordinary shapes or materials with similar compositions. [13][14][15][16][17][18] In this report, we extend our study to the NM structure with different metal compositions and sizes. This method allows us investigating the plasmon resonance behavior in symmetry-lacking structures.…”
Section: Introductionmentioning
confidence: 95%